Pelatihan Pelayanan Publik, Pengemasan dan Pemasaran Produk Warga Binaan Pada Lembaga Permasyarakatan Perempuan Kota Tangerang, Banten: PELATIHAN PELAYANAN PUBLIK, PENGEMASAN DAN PEMASARAN PRODUK WARGA BINAAN PADA LEMBAGA PERMASYARAKATAN PEREMPUAN KOTA TANGERANG - Nurhayati, Ida; yanto, Efri; Mirati, Elly; Vidyasari, Rahmanita (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2022)
Penitentiary as part of a government institution, one of its duties is to provide guidance for its residents. As part of a government institution, the purpose of this community service activity is that public service by correctional officers is one of the important elements that must be provided by government officials. Officers must always be oriented to the public interest by paying attention to the quality of services provided, so that the people served can provide positive responses. In addition to public service training for its apparatus, the target residents are given training in marketing and product packaging of works that have been produced by the assisted residents. The purpose of this service activity is so that the apparatus can provide maximum service to the inmates. Likewise for inmates after being released from prison, they can be productive, and apply the skills they have acquired while in prison. Thus, they can help the family economy which is carried out independently. The method is carried out by conducting excellent service socialization for prison officers. As for the assisted residents, it is carried out by means of interactive communication with the assisted residents so that it is more socialized and intensive. As a result, the apparatus can carry out more intensive and humane coaching. Likewise, the assisted residents can increase their knowledge of marketing and packaging to be more marketable.